CURRENT STATE OF THE PROBLEM OF INCREASE QUALIFICATIONS OF TEACHERS PHYSICAL EDUCATION (Pedagogy of Higher and Secondary Education, 2022)
The article is devoted to the modern problems of increasing qualification of physical training teacher.